Factors that affects email usage towards employees: a case study at Dewan Bandaraya Kuala Lumpur / Nur Mustika Zul - Zul, Nur Mustika (Faculty of Business and Management, 2013)
In this study, the researcher is focus on the factors that affects enlail usage towards employees: A Case Study at Tower 2, Dewan Bandaraya Kuala Lumpur (DBKL). The purpose of the study is to study the relationship between motivation, effective communication and the knowledge sharing with the email usage towards employees at Tower 2, Dewan Bandaraya Kuala Lumpur (DBKL). This research was conducted to learn how email can benefited to the organization and employees as well. This research emphasize on the purpose of conducting by examining how several factors lead to the employee's perception towards email usage such as motivation, effective communication, and knowledge sharing. For this study, strastified sampling technique were used and about 122 questionnaires were returned from 127 questionnaires given. The respondents were the employees at Tower 2, Dewan Bandaraya Kuala Lumpur (DBKL) and in this study several methods being used like descriptive analysis, frequency analysis, test of normality, reliability analysis, and pearson correlation. Based on the research, there are two factors; i.e effective communication and knowledge sharing indicate that there is positive relationships with factors that affect email usage towards employees. Meanwhile, motivation indicate that there are moderate relationship with the employee's perception towards email usage.